The Dilemma of Compliance - Chernykh, Svitlana (University of Michigan Press, 2024)
Over the past twenty years, the causes and consequences of post-election disputes have become one of the most compelling topics of research in political science. Between 2012 and 2022, political parties challenged the results of more than 25 percent of elections. When democratic transitions are dependent on the willingness of participants to accept defeat, political parties can undermine election-based democracy by rejecting the outcome. As the world enters the fourth decade since the start of the third wave of democratization, the question of whether election losers will comply or reject election outcomes is more and more pressing. The Dilemma of Compliance analyzes this phenomenon at the level of political parties, raising three important questions: Why do some political parties refuse to comply with election results? What determines the strategies they use to contest the outcomes? What consequences do post-election disputes have for the political parties that initiate them?